2019
DOI: 10.1021/acsnano.9b03531
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Clearable Porphyrinic Metal–Organic Framework Nanodots for Enhanced Photodynamic Therapy

Abstract: Nanoscale porphyrinic metal–organic frameworks (NMOFs) have emerged as promising therapeutic platforms for the photodynamic therapy (PDT) of cancer in recent years. However, the relatively large sizes of current NMOFs ranging from tens to hundreds of nanometers usually lead to inefficient body clearance and unsatisfactory PDT effect, thus amplifying their long-term toxicity and restricting their further usage. To overcome these shortcomings, herein, ultrasmall porphyrinic metal–organic framework nanodots (MOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 61 publications
0
58
1
Order By: Relevance
“…a) Schematic illustration of the preparation of MOF QDs with high‐efficiency renal clearance for cancer therapy. Reproduced with permission 38. Copyright 2019, American Chemical Society.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
See 2 more Smart Citations
“…a) Schematic illustration of the preparation of MOF QDs with high‐efficiency renal clearance for cancer therapy. Reproduced with permission 38. Copyright 2019, American Chemical Society.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
“…For another instance, Wang et al reported ultrasmall porphyrin-MOF nanodots (MOF QDs) with high ROS generation, efficient tumor accumulation, and rapid renal clearance in vivo, which could enhance the therapeutic effect of PDT and overcome the long-term toxicity (Figure 5a). [38] The MOF QDs were prepared from PCN-224 NMOFs via a liquid phase exfoliation method, and then PEG was modified on the surface by the coordination interactions between Zr 6 and the carboxyl Small 2020, 16,1906846 Reproduced with permission. [35] Copyright 2015, American Chemical Society.…”
Section: Multifunctional Mofs As Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Then they once again constructed nanorod and nanorice‐like Hf‐based NMOFs with diameters of about 80 nm . Recently, Qu and co‐workers have utilized ultrasonic processor to acquire Zr‐based MOF nanodots, which effectively accelerated the accumulation in tumor, and also had the characteristics of kidney clearance owing to their ultra‐small size . Anyhow, the effect of these different morphologies on the interaction between cells and nanomaterials including endocytosis and accumulation at tumors, and the biocompatibility of materials are not clear yet, which are worth further investigation for synthesizing NMOFs with more biological application value.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Reproduced with permission. [74] Copyright 2019, American Chemical Society. e) Nanocubes of Zr-MOFs.…”
Section: Imagingmentioning
confidence: 99%